Pengaruh Disiplin Kerja Dan Pengembangan Karir Terhadap Kinerja Pegawai Pada Dinas Pekerjaan Umum Dan Penataan Ruang (Pupr) Kota Ternate - Sofiya Rahakbau; Rahmat Sabuhari; Irfandi Buamonabot (Jurnal Pertanian Khairun, 2026)
This research is motivated by the challenges of human resource management in government agencies, particularly related to discipline and career development optimization, which directly impact organizational performance. The purpose of this study is to analyze the influence of work discipline and career development on employee performance at the Ternate City Public Works and Spatial Planning (PUPR) Department, both partially and simultaneously. The method used was a quantitative approach with a multiple linear regression analysis model using SPSS software. The study population consisted of 115 employees, and data collection was conducted through questionnaires. The results showed that partially, work discipline had a positive and significant effect on employee performance (t-test 3.698; sig. 0.000). Similarly, career development had a positive and significant effect on performance (t-test 9.560; sig. 0.000). Simultaneously, these two variables play a significant role in increasing organizational effectiveness. The study's conclusion confirms that the better the level of discipline and career development programs implemented, the higher the resulting performance. It is recommended that agencies continue to improve disciplinary oversight and transparency in promotions to maintain positive employee performance trends.